Hospital based dengue hemorrhagic fever surveillance management in Buleleng District, Bali during Covid-19 pandemic - I Gede Peri Arista; Anak Agung Sagung Sawitri; I Made Suganda Yatra (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2021)
Buleleng is district with the highest cases of Dengue Hemorrhagic Fever (DHF) in Indonesia on 2021. To reduce morbidity and prevent the event of the outbreak, it is necessary to evaluate the surveillance system. The purpose of this study was to evaluate the implementation of DHF surveillance in the Buleleng District. This research is a qualitative study conducted during the Covid-19 pandemic. The research location was in the Buleleng District to 27 informants consisting of one surveillance officer from the district health office and 26 surveillance officers from the hospitals and primary health care. Primary data collected using in-depth interviews and secondary data using document studies. This research uses the triangulation technique, analyzed of respondent characteristics was carried out using descriptive analysis assisted by IBM SPSS Statistics version 22 presented using tables and surveillance attribute analysis is carried out by data reduction presented in narrative form. The results showed that 11.1% of officers were still educated to high school, 25.9% of officers had never been trained, 92.6% of officers carried out multiple tasks, 3.7% of officers held programs under one year, 29.6% of officers were aged above 40 years, there is no budget for the empowerment of larva monitoring program, sensitivity and positive predictive value is quite low, data quality, acceptability, representativeness and stability are not optimal. The implementation of the surveillance has not been optimal due to limited manpower, cost and unfulfilled standards for several surveillance attributes. Reporting and diagnosis of cases need to be improved as the first step in efforts to prevent and control DHF.